TMOD-27. A NEURAL CREST CELL SUBPOPULATION UNDERLIES INTRATUMOR HETEROGENEITY IN MENINGIOMA. (11th November 2019) - Magill, Stephen; Vasudevan, Harish; Seo, Kyounghee; John Liu, S; Hilz, Stephanie; Villanueva-Meyer, Javier; Choudhury, Abrar; Demaree, Benjamin; Lim, Daniel; Braunstein, Steve; Ann Oberheim-Bush, Nancy; Ullian, Erik; et al.
Abstract: BACKGROUND: Meningiomas are the most common primary intracranial tumor, and high grade meningiomas are resistant to most cancer therapies. Intratumor heterogeneity is a recognized source of resistance to treatment in numerous malignancies. Thus, we hypothesized that investigating molecular heterogeneity in meningiomas would elucidate biologic drivers and shed light on tumor evolution and mechanisms of resistance. METHODS: We collected 86 spatially distinct samples at the time of resection from 13 meningiomas. Seven meningiomas were WHO grade I (46 samples), three were grade II (22 samples), and three were grade III (18 samples). Seven meningiomas were sampled at the time of salvage surgery (48 samples), and 6 were sampled at the time of initial diagnosis (38 samples). We performed multiplatform molecular profiling of these samples to identify drivers of intratumor heterogeneity, and validated our results using meningioma cells co-cultured with human cerebral organoids and RNA sequencing of paired primary and recurrent meningiomas. RESULTS: Using bulk RNA sequencing, DNA methylation profiling and phylogenetic analysis of spatially distinct samples, we discovered significant transcriptomic, epigenomic and genomic heterogeneity in meningioma. In particular, we identified chromosomal structural alterations and differences in immune and neuronal signaling that underlie clonal evolution in high grade tumors. Using MRI-stratified bulk RNA sequencing, single nuclear RNA sequencing, RNA sequencing of paired primary and recurrent meningiomas, and live cell microscopy and single cell RNA sequencing of meningioma cells in co-culture with human cerebral organoids, we revealed a rare meningioma cell subpopulation with strong transcriptional concordance to the neural crest, a multipotent embryonic tissue that forms the meninges in development. CONCLUSIONS: These data suggest that misactivation of a developmental cell population underlies intratumor heterogeneity in meningioma and that expression of neural crest and immediate early genes are an important step in meningeal oncogenesis.